Level of psychomotor abilities in handball goalkeepers - Krawczyk, P.; Bodasinski, S.; Bodasinska, A.; Slupczynski, B. (Baltic Journal of Health and Physical Activity, 2018)
Background: The results of previous studies indicate on a higher level of psychomotor abilities among players with a high sports level. The aim of the study was to evaluate the ability of selected psychomotor handball goalkeepers with a high level of sports